DECLINE AND INNOVATION OF UMRAH AGENCIES DURING PANDEMIC: A BECKΓÇÖS RISK SOCIETY PERSPECTIVE - Moh. Zaenal Abidin Eko Putro; M. Fakhruddin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2024)
Abstract This study examined the impact of the COVID-19 pandemic on Umrah Travel Organizers (PPIUs) in Bekasi City, West Java Province, Indonesia, focusing on their resilience and adaptation strategies in response to journey restrictions imposed by the Saudi Arabian government. Using Ulrich BeckΓÇÖs risk society theory, the research analyzes the effects of Umrah journey restrictions and explores how PPIUs in Bekasi City adjusted their operations. Qualitative methods, including observation, document analysis, and in-depth interviews conducted between September and October 2021, were employed to explore this phenomenon deeply. This approach facilitated a comprehensive understanding of how the pandemic led to operational declines among PPIUs and prompted innovations within the sector. The closure of Saudi ArabiaΓÇÖs borders to Umrah pilgrims from Indonesia significantly impacted PPIUs, resulting in financial strain and operational crises. While some PPIUs managed to adapt through effective risk management and diversification of business activities, others faced closure due to financial losses. The study highlights the diminishing influence of state actors in controlling Umrah travel, underscoring the increasing role of non-state actors and digital platforms in the industry. This research contributes to the literature on the vulnerability of religious tourism during global crises and emphasizes the importance of adaptive strategies within the PPIU sector. Future research should focus on developing sustainable practices and innovations to enhance resilience against similar challenges, providing a foundation for practical applications in the field of religious tourism and risk management. Abstrak Penelitian ini mengkaji dampak pandemi COVID-19 terhadap Penyelenggara Perjalanan Umrah (PPIU) di Kota Bekasi, Provinsi Jawa Barat, Indonesia, dengan fokus pada strategi ketahanan dan adaptasi mereka dalam menanggapi pembatasan perjalanan yang diberlakukan oleh pemerintah Arab Saudi. Dengan menggunakan teori risk society dari Ulrich Beck, penelitian ini menganalisis efek pembatasan perjalanan Umrah dan mengeksplorasi bagaimana PPIU di Kota Bekasi menyesuaikan operasinya. Metode kualitatif, termasuk observasi, analisis dokumen, dan wawancara mendalam yang dilakukan antara September dan Oktober 2021, digunakan untuk mendalami fenomena ini. Pendekatan ini memfasilitasi pemahaman komprehensif tentang bagaimana pandemi menyebabkan penurunan operasional di kalangan PPIU dan mendorong inovasi dalam sektor tersebut. Penutupan perbatasan Arab Saudi bagi jamaah Umrah dari Indonesia berdampak signifikan pada PPIU, menyebabkan tekanan keuangan dan krisis operasional. Sementara beberapa PPIU berhasil beradaptasi melalui manajemen risiko yang efektif dan diversifikasi aktivitas bisnis, yang lain menghadapi penutupan karena kerugian keuangan. Studi ini menyoroti berkurangnya pengaruh aktor negara dalam mengendalikan perjalanan Umrah, dengan menekankan peran meningkatnya aktor non-negara dan platform digital dalam industri ini. Penelitian ini berkontribusi pada literatur tentang kerentanan pariwisata religius selama krisis global dan menekankan pentingnya strategi adaptif dalam sektor PPIU. Penelitian masa depan sebaiknya berfokus pada pengembangan praktik berkelanjutan dan inovasi untuk meningkatkan ketahanan terhadap tantangan serupa, memberikan landasan untuk aplikasi praktis dalam bidang pariwisata religius dan manajemen risiko.